Hydrocarbon Reservoir Characterization Based on the Integration of AVO and Fluid Replacement Modelling (FRM): A Case Study of the FR Field, Balikpapan Formation - Andhira Djafniel Yudanur; A. Haris; Said Sabbeq (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to characterize potential gas-bearing reservoir zones in the FR Field within the Balikpapan Formation, Kutai Basin, through the integration of Amplitude Versus Offset (AVO) analysis and Fluid Replacement Modelling (FRM) using a single-well dataset. The Balikpapan Formation in the Kutai Basin is known for its complex stratigraphic and lithological heterogeneity, which poses challenges for seismic interpretation. The three-dimensional (3D) pre-stack seismic gathers were processed to preserve true amplitude for reliable AVO analysis. Intercept and gradient attributes were extracted to identify Class III AVO anomalies linked to gas-saturated sandstone. Validation was carried out using FRM based on well log data (Vp, Vs, and density) by simulating elastic property changes under different fluid conditions using Gassmann’s equation. The FRM results indicate a decrease in P-wave velocity and Poisson’s ratio under gas-saturated conditions, consistent with AVO responses. AVO attribute maps further depict the lateral distribution of zones prone to gas, offering valuable insights for well placement and field development strategies. The integration of AVO and FRM effectively reduces interpretation uncertainty and improves the understanding of reservoir characteristics within the Balikpapan Formation.